Collaborative Co-Teaching of Islamic Education and Counseling Teachers in Strengthening Students Religious Character - Susanto Susanto; Muhammad Yunan Harahap (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
The decline in students’ religious character and moral behavior reflects a growing gap between the spiritual values promoted in schools and students’ actual conduct. This study aims to explore how collaborative co-teaching between Islamic Education and Counseling teachers can strengthen students’ religious character at SMA Panca Budi Medan. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation involving teachers, students, and administrators. The findings show that the co-teaching model—implemented through joint planning, teaching, and evaluation—fosters an integrative approach combining spiritual guidance and psychological support. Islamic Education teachers emphasize moral and spiritual values, while Counseling teachers facilitate reflection and emotional awareness. This collaboration enhances students’ religiosity, empathy, discipline, and participation in religious activities. The model also improves teacher professionalism through mutual learning and shared reflection. However, challenges remain, including scheduling constraints and differing pedagogical paradigms. The study implies that co-teaching offers a transformative framework for character education in Islamic schools, promoting holistic, contextual, and value-based formation of students’ religious identity.